2001
DOI: 10.1172/jci200113505
|View full text |Cite
|
Sign up to set email alerts
|

Role of AMP-activated protein kinase in mechanism of metformin action

Abstract: Methods Measurements of AMPK, ACC, and fatty acid oxidation in primary hepatocytes.Hepatocytes were isolated from male Sprague Dawley (SD) rats by collagenase digestion (18). For the AMPK assay, cells were seeded in six-well plates at 1.5 × 10 6 cells/well in DMEM containing 100 U/ml penicillin, 100 µg/ml streptomycin, 10% FBS, 100 nM insulin, 100 nM dexamethasone, and 5 µg/ml transferrin for 4 hours. Cells were then cultured in serum-free DMEM for 16 hours followed by treatment for 1 hour or 7 hours with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,495
11
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,480 publications
(1,583 citation statements)
references
References 28 publications
51
1,495
11
26
Order By: Relevance
“…Immunoblots were performed against phospho-ACC (Ser79), phospho-AMPKα (Thr172), AMPKα, and β-actin. (4,7,24). Although direct evidence of colocalization of AMPK and OCTs in a specific cell is not available, we observed that the activation of AMPK by metformin was enhanced in cell lines (or transfected cells) that exhibited OCT activity, suggesting that the tissue-specific action of metformin may be related to expression of influx transporters such as OCTs that can deliver metformin intracellularly.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Immunoblots were performed against phospho-ACC (Ser79), phospho-AMPKα (Thr172), AMPKα, and β-actin. (4,7,24). Although direct evidence of colocalization of AMPK and OCTs in a specific cell is not available, we observed that the activation of AMPK by metformin was enhanced in cell lines (or transfected cells) that exhibited OCT activity, suggesting that the tissue-specific action of metformin may be related to expression of influx transporters such as OCTs that can deliver metformin intracellularly.…”
Section: Discussionmentioning
confidence: 70%
“…Quinidine, an OCT inhibitor, decreased the phosphorylation of AMPK and ACC by metformin in wild-type hepatocytes ( Figure 4C). Downstream, metformin-stimulated AMPK phosphorylation results in a decrease in hepatic gluconeogenesis (4,7). Metformin (1 mM) significantly suppressed glucagon-stimulated glucose production in hepatocytes from wild-type mice (30% suppression; P < 0.001) but not in hepatocytes from Oct1 -/-mice ( Figure 4D).…”
Section: Oct Activity Is a Determinant Of Metformin Response In Cell mentioning
confidence: 98%
See 3 more Smart Citations